Analisis Penerapan Akuntansi Manajemen Dalam Meningkatkan Efisiensi Pengelolaan Keuangan Perusahaan - Achmad Fauzi; Angel Septiani Parhusip; Annisa Hediana; Hanifah Adilla Putri; Rani Anggitasari; Sephia Supriyadi; Yudho Hari Rahmat (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
Analysis of the application of management accounting to improve the efficiency of corporate financial management. This study aims to determine how management accounting is used in improving the efficiency of the company's financial management. The research method used is descriptive qualitative analysis. The results showed that management accounting plays an important role in improving the efficiency of the company's financial management. Management accounting allows managers to make better and more effective decisions in managing the company's finances. In addition, management accounting also helps in identifying and handling financial problems that arise so as to improve the efficiency of financial management of a company. This study investigates how management accounting can help companies manage finances efficiently